Mengawal Risiko untuk Akuntabilitas: Literasi Arsip sebagai Instrumen Administrasi Publik Berkelanjutan - Rutina Dwi Wahyunengseh; Didik Gunawan Suharto; Sudarmo Sudarmo; Faizatul Ansoriyah; Wahyu Nurharjadmo; Ryza Dani Pratiwi; Agusniar Rizka Luthfia (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2026)
This article discusses the strengthening of archive governance in regional apparatus organizations in Magelang City as part of the Community Service (PkM) program of Sebelas Maret University in collaboration with the Magelang City Library and Archives Office. Although Magelang City has achieved an A grade in archival supervision from the National Archives of the Republic of Indonesia, various challenges are still found, such as the preparation of dynamic archive lists that are not optimal, not all Regional Apparatus have submitted static archives, and the integration of digital systems in most OPDs is not optimal. In addition, the application of the SRIKANDI (Sistem Informasi Kearsipan Dinamis Terintegrasi/ Integrated Dynamic Archiving Information System) application is also uneven and has not been used optimally as an institutional information management tool. This service activity is carried out through a collaborative and participatory approach, with strategies in the form of archival culture seminars, focused discussions with heads of regional apparatus and department secretaries, and a review of the results of archival supervision audits. The main focus of this activity is to build institutional awareness, formulate steps to mitigate the risk of losing archives, and increase human resource capacity in digital-based archive management. The results of the activity showed an increase in the apparatus' understanding of the archive cycle and the development of recommendations for saving institutional archives. This activity strengthens the role of the archives office as a node to save organizational memory while bridging the gap between national policy and archive management practices at the regional level. The practical implication of this activity is the increased readiness of the regional bureaucracy in facing digital transformation and demands for sustainable public accountability in the field of archives.